DAMPAK MOTIVASI KERJA DAN PERSEPSI KOMPENSASI TERHADAP KINERJA KARYAWAN PT SAMASTA BOGA INDONESIA - Ulfa Febriana; Itsna Nurrahma Mildaeni; Nur’aeni Nur’aeni; Herdian Herdian (CV. Denasya Smart Publisher, 2025)
Suboptimal employee performance remains a major issue at PT Samasta Boga Indonesia. This condition is suspected to be affected by low work motivation and unfavorable perceptions of compensation. This study adopted a quantitative approach using total sampling, involving 130 employees. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS 26. The results indicate that work motivation has a significant effect on performance (p 0.05), contributing 9.1%, and compensation perception also has a significant effect (p 0.05), contributing 17%. Simultaneously, both variables significantly affect employee performance (F = 16.288; R = 0.204), meaning that together, work motivation and compensation perception contribute 20.4% to employee performance. The findings confirm that work motivation and compensation perception play crucial roles in improving employee performance. Therefore, company management should optimize these factors as part of their strategy to enhance productivity.